Pengaruh Vidio Edukasi tentang Personal Hygiene Saat Menstruasi terhadap Tingkat Pengetahuan Remaja Awal (Early Adolescence) - Ima Tareza; Tia Nurhanifah; Kristina Maharani (Lembaga Pengembangan Kinerja Dosen, 2024)
The incidence of reproductive tract infections (RTI) in adolescents around the world ranks between 35% and 42%. According to data from the Indonesian Ministry of Health, as many as 5.2 million adolescents complain of itching in the genital region after menstruation, which is a result of poor personal hygiene during menstruation. This situation exists because the level of knowledge of adolescents is lacking, especially among those who have just experienced menstruation. Adolescents' lack of knowledge about personal hygiene is the leading cause of high cases of reproductive tract infections. This study aimed to determine the effect of educational videos about personal hygiene during menstruation on the level of knowledge in early adolescence. This type of research is a quantitative study with a pre-experimental method and a one-group pre-test-post-test design. The population in this study were early adolescents in class VII at the Al Badriyyah Mranggen Islamic Boarding School who were already menstruating. The sampling technique used total sampling and obtained 47 female students. The instrument used in this research is a questionnaire. Data analysis was carried out in terms of univariate and bivariate analysis (using the McNemar test with a p-value < 0.05). The results of this study showed that educational videos about personal hygiene during menstruation were affected by the level of knowledge in early adolescence, with a p-value of 0.001 < 0.05.